Utilization of Waste Paper Sludge as an Alternative Adsorbent for the Adsorption of Ammonia Nitrogen and COD in Stabilized Landfill Leachate - Daud, Zawawi; A Rahman, Shahril Effendi; Awang, Halizah; Abubakar, Mahmoud Hijab; Ridzuan, Mohd Baharudin; Tajarudin, Husnul Azan (International Journal of Integrated Engineering, 2019)
Waste paper sludge (WPS) is produced by the paper industry during the wastewater treatment process of paper production. The disposal techniques of WPS pose a great concern for the environment. This study focuses on the evaluation of WPS as an alternative absorbent material to activated carbon (AC) for the removal of contaminants from stabilized landfill leachate. Ammonia nitrogen (NH3-N) and chemical oxygen demand (COD) were identified as the two major contaminants in landfill leachate. Both AC and WPS were mixed together in different ratios. The optimum replacement for the absorbent was determined using the batch technique. The adsorption batch study was carried out under the optimum pH of 7, with a shaking speed of 200 rpm and a contact time of 120 minutes. The adsorption isotherms indicated that the Langmuir model was better fitted to the experimental data as it was found to have the highest regression values. The Langmuir adsorption capacities for COD and NH3-N were 32.26 mg/g and 21.60 mg/g, respectively. The optimum replacements were initially at two different ratios of 2:2 and 3:1 based on the optimum removal of COD and NH3-N, respectively. However, the final optimum replacement for the absorbents (AC: WPS) in this study was the ratio of 2:2 due to the higher removal of COD (85.9%) and NH3-N (49.3%).